Women's experiences with information provision and deciding about fertility preservation in the Netherlands: 'satisfaction in general, but unmet needs'. (5th May 2013) - Garvelink, Mirjam M.; ter Kuile, Moniek M.; Bakker, Rinske M.; Geense, Willemijn J.; Jenninga, Esther; Louwé, Leoni A.; Hilders, Carina G. J. M.; Stiggelbout, Anne M.
Abstract: Objective: It is not well‐known how women receiving counselling consultation about fertility preservation (FP) in the Netherlands perceive the information provision about and referral for FP in the oncology setting. The aim of this study was to qualitatively explore women's experiences with the (process of) information provision about the gonadotoxic effects of cancer treatment and about FP and the decision‐making process and to obtain their recommendation for improvements. Methods: Semi‐structured interviews with female patients with cancer who had received a counselling consultation on FP (at 18–40 years of age). Results: Thirty‐four interviews were held (response rate 64%). Information provision was considered to be important. Overall, women were satisfied with the timing and the content of the information, but women were less positive about the need to be assertive to get information, and the multiplicity of decisions and actions to be carried out in a very short time frame. Conclusions: Information provision on gonadotoxic effects of cancer treatment and about FP was overall deemed sufficient, timely and important. Women recommended standardization of the information provision, improvement of communication among clinicians and medical centres, and availability of FP‐specific patient information materials to improve future information provision processes.